Proses Pembelajaran Pendidikan Jasmani Adaptif Anak Berkebutuhan Khusus Anak Tunagrhita di SLB Negeri Cendono Kabupaten Kudus (Indonesian Journal for Physical Education and Sport, 2022)
The right to obtain the same education is owned by all individuals, therefore education is not only intended for normal children but also for children with special needs. In relation to physical education, children with special needs are also entitled to physical education learning like normal children in general, in a way that has been adapted to the conditions of each child with special needs. This study was structured with the aim of knowing the physical education learning process for children with special needs for mentally retarded children at SLB Negeri Cendono, Kudus Regency which includes the learning planning process, the learning implementation process, and the learning assessment process. The method used in this study is a qualitative method with a descriptive approach. The results of this study are the learning planning process begins with making the syllabus and lesson plans, the learning implementation process is carried out in the classroom and in the field adjusted to the situation and conditions at the time of the learning implementation, the learning assessment process is carried out by looking at the affective, cognitive, and psychomotor aspects. The conclusion from the research on the adaptive physical education learning process for children with special needs at SLB Negeri Cendono, Kudus Regency is good.